PENGARUH STRATEGI CUSTOMER RELATIONSHIP MARKETING (CRM) DAN KEBIJAKAN DISKON TERHADAP LOYALITAS PELANGGAN GREENFIELDS DI PT. EKA PUTRA PEKANBARU - Zainur , Nabila Syamara; Othman, Lie (Komunitas Manajemen Kompetitif, 2025)
Abstract: The purpose of this study is to find out further how the loyalty of Greenfields milk customers at PT. Eka Putra Pekanbaru related to customer relationship marketing strategy and discount policy. Customer relationship marketing and discount policy become independent variables while customer loyalty becomes dependent variables. Problems that occur in PT. Eka Putra is a decrease in the number of product purchases as evidenced by the non-achieval of the company's target, as well as the presence of several customers who switch to competing companies. The sample in this study was determined using the slovin formula obtained, namely 88 respondents. This type of research is quantitative research using questionnaire data collection techniques by spreading questionnaires. The data obtained from the survey results was tested with the SPSS 25 program. The test results showed that customer relationship marketing had an influence on customer loyalty, where = 10.625 > 1.662 and sig 0.000 < 0.05. Furthermore, the discount policy has an influence on purchase loyalty, where = 12.180 > 1.662 and sig 0.000 < 0.05, as well as customer relationship marketing and discount policy on customer loyalty with of 91,920 > 3,100 with sig 0.000 < 0.05. Keywords : Customer relationship marketing, Discount policy, Customer loyalty, PT. Eka Putra Pekanbaru, Quantitative